Обробка рукописного тексту з зображень - Бутенко, П. В. (ХНУРЕ, 2024)
This study focuses on the efficiency of handwriting processing in images. The main emphasis is placed on the use of image binarization, segmentation, and the Hidden Markov Model algorithm. The study aims to identify key processing steps that help improve the quality of handwriting recognition. The current context of the information society emphasizes the importance of this kind of research, as the transfer of documents into electronic format is still a pressing task
Keywords: обробка рукописного тексту; рукописний текст